Impact of infection on admission and of the process of care on mortality of patients admitted to the Intensive Care Unit - Gonçalves-Pereira, J. (2014)
Funding Information: Financial support: this work was supported by an unrestricted grant from GIS (Grupo de Infecção e Sepsis, Hospital de São João, Porto, Portugal). Publisher Copyright: © 2014 European Society of Clinical Microbiology and Infectious Diseases2012 December 2014 10.1111/1469-0691.12738 Original Article INFECTIOUS DISEASES Original Articles © 2014 The Authors Clinical Microbiology and Infection © 2014 European Society of Clinical Microbiology and Infectious Diseases.